Peripheral inflammatory and regulatory immune changes in HIV positive to HIV positive renal transplant recipients - Rautenbach, Stefan (Institute of Infectious Disease and Molecular Medicine, 2019)
INTRODUCTION Since 2008, 43 renal transplants have been performed from HIV positive deceased donors to HIV positive recipients with renal failure predominantly due to HIV-associated Nephropathy (HIVAN). Recipients received Anti-thymocyte globulin (ATG) induction therapy and maintenance immunosuppression. Despite transplantation across Human Leukocyte Antigen (HLA) mismatches, there were few rejection events in the first year post-transplant (PT). Recipient CD4 counts did not decrease and HIV viral load also remained undetectable at one year PT. To gain insight into immune homeostatic mechanisms after ATG induction, immunosuppression and transplantation, a subset of 10 transplant recipients were investigated. This dissertation examined levels of peripheral inflammatory and regulatory cytokines. A polychromatic flow cytometry panel was also developed to measure the phenotypic T cell proportions of T regulatory cells (Tregs) in the blood circulation. METHODOLOGY A multiplexed Luminex assay was used to measure the concentrations of 67 inflammatory and regulatory plasma cytokines immediately pre-transplant, at 1, 3, 6 and 12 weeks PT. Two separate manufacturers of Luminex panels were used and a series of statistical analyses were employed to identify intra- and interplate variation. Firstly, data was cleaned up by excluding analytes for which >90% of measured values were outside of the observable range of the standard curve. Secondly, the measurable values were assessed for differences between replicates (intra-plate variation). A Bland-Altman plot was used to identify and exclude highly divergent replicates of the same sample. Thirdly, a Paired Ttest/Wilcoxon Signed Rank Test was used to investigate differences between inter-plate controls (inter-plate variation). Fold change from baseline was calculated for all values to correct for inter-plate variability. After correcting for variability, fold change trends in all included analytes were examined for each recipient. Trends in recipients with rejection events (rejectors) and recipients without rejection events (non-rejectors) were also compared. Fold change from baseline was assessed to identify single analytes that differed over time using a Paired T-test/Wilcoxon Signed Rank Test. A hierarchical clustering analysis (HCA) was used to identify groups of analytes for which fold change may have been significantly influenced by age, sex, baseline CD4 count at transplantation (TP), number of HLA matches, or time. A mixed effect generalised linear model (MEGLM) was constructed to calculate differences between participants for each cytokine. A polychromatic flow cytometry panel was devised to measure Treg CD4+ T cells consisting of the following antibodies: CD3-BV650, CD4-PE/Cy5.5, CD8- HorizonV500, CD27-PE/Cy5, CD45RA-PerCP/Cy5.5, CD25-BV421, CD127- PE/CF594, and FoxP3-Alexa647. Antibody concentrations in the panel were optimised by titrating each marker on resting, or Phytohaemagglutinin (PHA) stimulated, peripheral blood mononuclear cells (PBMCs). The median fluorescent intensity (MFI) of the positive and negative populations for each marker was used to calculate the signal:noise ratio for all titrating volumes. The optimal volumes were determined by the highest signal:noise ratio for each marker. RESULTS In all recipients, when compared to baseline, IL-2, IFN-α2 and IFN-γ were significantly decreased at 12-weeks PT. IL-35 was significantly decreased at weeks 1, 3, 6 and 12 PT, whilst IL-10 increased significantly at 1-week PT in 5 recipients. Hierarchical clustering showed no association with analyte fold changes due to age, sex, CD4 count, or number of HLA matches. It did show a decrease over time in IL-35, IFN-γ, IL-20, IL-28A, and IL-11 for all 10 recipients. A mixed-effects generalized model (MEGLM) was used to identify analytes with variable concentrations between recipients. It showed that the concentrations of IL-28A, IL-6Rα, IL-6Rβ, sTNFR1, Pentraxin-3 and IFN-γ varied the most between recipients. IL-35 and TNFSF12 were shown to vary the least between recipients. These data suggest heterogeneity in the highly variable analytes, none of which were shown to differ over time. The heterogeneity is likely due to genetic diversity, history of opportunistic infections and relevant prophylaxis. The concentrations of IL-35 did not vary between recipients, but it was shown to decline over time in all recipients. This data suggests a consistent decline in the concentration of IL-35 in all recipients over the first 12-weeks PT. An 8-colour Regulatory T cell (Treg) flow cytometry panel was designed based on the Luminex results and optimised to phenotype peripheral T-cell subsets. It distinguished between different T-cell phenotypes, namely naïve and memory, CD4 or CD8, and activated and regulatory T cells. Antibody titrations identified the optimal volume of each marker to use in a combination cocktail. Due to time constraints, the panel was not used on patient material, but the panel and its optimisation has been described in detail. CONCLUSIONS Statistical investigations into the Luminex results identified variability between replicates and between plates. These differences needed to be accounted for before combining data between plates and kits to arrive at biological conclusions. By using stringent analysis, this dissertation shows that multiplex data is highly variable and a series of statistical approaches should be employed to avoid including erroneous data. A decrease in both inflammatory and regulatory proteins was shown in the 12 weeks after transplantation and ATG induction. The transient increase in IL-10 suggested the induction of effector T-cells to become IL-10 producing Tregs (Tr1), known to occur in response to ATG induction. Combined with the consistent decline in IL-35 in all recipients, these results suggested that there was preferential secretion of IL-10 over IL-35 in some patients early after transplantation.